Pengaruh Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Pegawai pada RSUD Kondosapata Kabupaten Mamasa - Mirnawati limbong lebok; Azhari Azhari; Ansar Mulkin (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This research aims to determine the influence of leadershi and work discipline on employe performance at Hospital kondosapata kabupaten mamasa.Using multiple linear regression analysis type of research used is quantitative research by distributing questionnaires via Google From.Sampling technique, where the number of samples was the some as the population,namely fourteen people.The results of the test analysis (partial) can be concluded ha there is a positive and significant influence of the leadership variabel on employe permomance,with can be seen from the t value of 6.454> t table 2.024 with a significan level of 0.000< 0.05,and it can also be concluded that there is a positive and significan influence of the employe work discipline variabel on employee performance by looking at the tcount value of 4.275 > table 2.024 and the significant level of 0.000 > 0.05.As for the results of results of the test (simultaneous), it can be concluded hat leadership and work discipline simultaneous have a positive and significan effect on employe perfomane.